First-Year Real-Life Experience with Intravitreal Faricimab for Refractory Neovascular Age-Related Macular Degeneration - Wissam Aljundi; Loay Daas; Shady Suffo; Berthold Seitz; Alaa Din Abdin (MDPI AG, 2024)
Background: To evaluate the outcomes of intravitreal faricimab (IVF) for refractory neovascular age-related macular degeneration (nAMD) and investigate the impact of baseline optical coherence tomography, biomarkers for total IVF injections are needed. Methods: A retrospective analysis of 33 eyes of patients who completed one year (52 W) of treatment with IVF. The eyes received four IVF injections (6 mg/0.05 mL) as the upload phase. Thereafter, the treatment interval was extended to 8 or 12 weeks if disease activity was not recorded. The outcome measures included best-corrected visual acuity (BCVA), central macular thickness (CMT), subfoveal choroidal thickness (SFCT), and retinal fluid distribution. Results: A total of 33 eyes were included. CMT decreased significantly at 52 W (p < 0.01). BCVA and SFCT did not change significantly at 52 W (p > 0.05). The number of eyes with subretinal fluid decreased significantly at 52 W (p < 0.01). Complete fluid resolution was achieved in 20 eyes (60%). The total number of injections was significantly negatively correlated with the presence of hyperreflective dots at baseline (HRDs, p < 0.01) and SFCT at baseline (p < 0.01). Conclusions: IVF led to a significant reduction in CMT with stabilization of BCVA. The total number of injections was lower in eyes with HRDs and increased SFCT at baseline. This might provide clues regarding response to IVF for future studies.